Emerging 2D MXene-based polymeric membranes for water treatment and desalination - Saniha Ajith (15954329) (2024)
Amidst rapid urbanization and population growth, the global concern over freshwater scarcity is escalating. Addressing this challenge requires a shift toward alternative water treatment technologies. In recent times, there has been a noteworthy surge in the application of innovative 2D nanomaterials MXenes for water treatment. These materials, with chemical formula Mn+ 1AXn, originating from the precursor MAXene by eliminating the A element, showcasing structural similarities to graphene and other 2D layers. Despite numerous studies incorporating MXenes into polymeric membranes for water desalination and treatment, a comprehensive review of the relevant literature is lacking. This review delves into past and current studies on MXene-based polymeric membranes for water treatment, offering insights into their structure, synthesis, and properties. MXenes, with their substantial surface area, hydrophilic nature, high conductivity, and customizable surface chemistry, hold the potential to revolutionize water filtration. Their incorporation into membranes contributes to increased water flux, enhanced rejection rates for salts and dyes, augmented surface hydrophilicity, and improved overall membrane efficiency. The main mechanisms governing MXene-based polymeric membrane function are size exclusion and the Donnan exclusion. Despite the promise of MXenes, challenges such as complex fabrication methods, instability, and economic concerns persist. Ongoing research focuses on standardized methods, alternative MXene variants, and establishing rigorous benchmarks for large-scale adoption to address these obstacles. Continued research efforts are essential for refining fabrication methods, optimizing membrane composition, and expanding applications to unlock the full potential of MXene-based membranes for sustainable water treatment. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2024.112078